Biomimetic and Concise Total Syntheses of Prenylated and Bicyclo[2.2.2]diazaoctane-Containing Indole Alkaloids Including Taichunamide A, Notoamide N and Versicolamide B - Xu, Zhongnan; Liang, Xin-Ting; White, Lorenzo V.; Banwell, Martin G.; Tan, Shen (Journal of organic chemistry, 2024)
Total syntheses of the title prenylated indole alkaloids together with seven others are reported. Biogenetic considerations have been employed in devising the reaction sequences leading to these targets with, in the opening stages, electrochemically-derived indole-3-carboxaldehyde 15 being subject to an aldol-type condensation reaction involving diketopiperazine derivative 19. This led, after prototopic shifts, intramolecular Diels–Alder cycloaddition and hydrolysis/deprotection steps, to the racemic forms of the bicyclo[2.2.2]diazaoctane-containing natural product stephacidin A (2) and its C6 epimer 3. Epoxidation of the last compound afforded, following rearrangement of the primary oxidation products, a mixture of (±)-taichunamide A [(±)-4] and (±)-versicolamide B [(±)-7]. Related protocols allowed for the conversion of (±)-stephacidin A [(±)-2] into (±)-notoamide B [(±)-5]. Analogous aldol condensation, nucleophilic reduction, and epoxidation steps led to the formation of (−)-notoamide E and its conversion into notoamide C as well as the indole fragmentation product amoenamide E. A late-stage chlorination reaction applied to (±)-stephacidin A provided access to the spirocyclic oxindole (±)-notoamide N [(±)-6].